2022
DOI: 10.2147/idr.s379502
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm-Associated Multi-Drug Resistance in Hospital-Acquired Infections: A Review

Abstract: Biofilm-related multi-drug resistance (MDR) is a major problem in hospital-acquired infections (HAIs) that increase patient morbidity and mortality rates and economic burdens such as high healthcare costs and prolonged hospital stay. This review focuses on the burden of bacterial biofilm in the hospital settings, their impact on the emergence of MDR in the HAIs, biofilm detection methods, recent approaches against biofilms, and future perspectives. The prevalence of biofilm-associated MDR among HAIs ranges fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 57 publications
0
33
0
Order By: Relevance
“…The relevance of the consequences of biofilm formation and drug resistance to the severity of the infection [ 37 ] prompted us to delve deeper into the characteristics of the strains and compare the different traits among them. We showed that the multidrug resistance profile of isolates was significantly more frequent in the group of strains capable of biofilm formation on CRA when compared to the non-biofilm forming group ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The relevance of the consequences of biofilm formation and drug resistance to the severity of the infection [ 37 ] prompted us to delve deeper into the characteristics of the strains and compare the different traits among them. We showed that the multidrug resistance profile of isolates was significantly more frequent in the group of strains capable of biofilm formation on CRA when compared to the non-biofilm forming group ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, with the advancement of medicines, such as humans, microorganisms, such as bacteria, have also gone through numerous evolutions to thrive in harsh and foul environments [ 16 , 17 ]. Bacteria can form biofilms, which are a plethora of different species living under a matrix made up of exopolysaccharides (EPS) that can protect themselves from the harmful effects of traditional antibiotics, AgNPs, and Ag + due to its complex structure [ 18 , 19 , 20 , 21 ]. Hence, the same concentration of AgNPs usually effective against planktonic bacteria will not work the same against bacteria protected in a biofilm [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial biofilm formation (BBF) is usually a multi-step process, involving the attachment of the bacteria to the substrate, the formation of microcolonies, the growth and maturation of the microcolonies into the mature biofilm and finally the dispersion of the mature biofilm [ 1 , 2 , 3 ]. In recent years, new data have shown the frequent involvement of biofilms in human pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, new data have shown the frequent involvement of biofilms in human pathologies. Examples of biofilm mediated infections include endocarditis, prosthetic device infections, and catheter-related urinary tract infections and bacteremia [ 1 , 4 , 5 , 6 , 7 , 8 ]. Unsurprisingly, there is a brand-new worldwide trend to study BBF, its involvement in human infections and the means of eradication.…”
Section: Introductionmentioning
confidence: 99%